Liver Function Tests During the Perinatal Period - Onwuameze IC.. (Nigerian Journal of Paediatrics)
Summary: Serum iso-citrate dehydrogenase (ICD), aspartate transaminase (AST), alkaline phosphatase (ALP) gamma-glutamyli deter transferase (GGT), total bilirubin, total protein and albumin were deter mined and compared in 68 paired maternal and corresponding cord blood EST and in 70 age-matched non-pregnant females. The subjects were without previous history or physical findings of liver disease. The data show that sekot the levels of AST, ALP, GGT and total bilirubin were significantly higher than in cord blood (p<0.001) than in either maternal or non-pregnant female ROF. blood. Serum total protein and albumin were however significantly lower in cord blood (p<0.001) than in either maternal or non-prenant female TU blood. The significance of the finding especially in the interpretation of liver function tests in the neonate is discussed.